2018
DOI: 10.1016/j.jsbmb.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone complex and non-steroidal ligands of human aromatase

Abstract: Cytochrome P450 aromatase (AROM) catalyzes the biosynthesis of estrogen from androgen. Previously crystal structures of human AROM in complex with the substrate androstenedione, and inhibitors exemestane, as well as the newly designed steroidal compounds, have been reported. Here we report the first crystal structure of testosterone complex of human placental AROM. Testosterone binds at the androgen-specific heme distal pocket. The polar and hydrophobic interactions with the surrounding residues resemble the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…This parallel pose has been comparatively observed for steroidal ligands binding to CYP19A1 (e.g. PDB 3EQM, 5JKW; (Ghosh et al, 2018)).…”
Section: D4a (Supplementalmentioning
confidence: 65%
“…This parallel pose has been comparatively observed for steroidal ligands binding to CYP19A1 (e.g. PDB 3EQM, 5JKW; (Ghosh et al, 2018)).…”
Section: D4a (Supplementalmentioning
confidence: 65%
“…This pocket shows similitude to the cavity used by testosterone in the aromatase (an enzyme that also binds testosterone to convert it into 17β estradiol) [ 183 ]. Additionally, it has been reported that testosterone binds to the AR through a H-bond with an arginine (R752) [ 184 ], similarly to the H-bond predicted for the interaction with the TRPM8 channel.…”
Section: A Brief Structural View Of the Steroid Pocket In Some Trpmentioning
confidence: 99%
“…Because DHT is highly similar to TES in both chemical structure and conformation, the initial CYP3A4‐DHT complexes were obtained by superimposing DHT onto each of the top‐ranked TES poses. The initial structure of the CYP19A1‐TES complex was taken from the crystal structure (PDB code: 5JKW) . Similarly, DHT was superimposed to TES to obtain the CYP19A1‐DHT complex.…”
Section: Methodsmentioning
confidence: 99%
“…The initial structure of the CYP19A1-TES complex was taken from the crystal structure (PDB code:5 JKW). [49] Similarly,D HT was superimposed to TES to obtain the CYP19A1-DHT complex.…”
Section: Experimental Section Molecular Dockingmentioning
confidence: 99%